Metrobank Foundation exemplars - Lee, Queena N. (Makati City Metrobank Foundation, 2012)
Profiles of 15 outstanding teachers, soldiers, police officers, artists and journalists.
Includes bibliographical references.
Keywords: Metrobank Foundation, Inc. -- History; Successful people -- Philippines -- Biography; Role models -- Philippines; Conglomerate corporations -- Philippines -- History; Philippines -- Biography